Reputation Management Strategy of Natural Bengkulu Logo as a Regional Tourism Brand - Lisa Adhrianti; Rafinita Aditia (Ikatan Sarjana Komunikasi Indonesia, 2025)
In an effort to overcome the weak tourism reputation management in Bengkulu Province, the Bengkulu Provincial Tourism Office has taken a bold step by launching a new tourism brand, namely the Natural Bengkulu logo. Although this effort is expected to provide a strong visual identity, new challenges arise when people only see the logo as an attractive visual element without understanding the deep philosophy that should be the foundation of a tourism brand. A tourism brand is not just a visual representation or logo, but includes values, stories, and experiences that can shape positive perceptions of a destination. This study aims to analyze brand reputation management strategies through a qualitative descriptive approach with a case study method. The focus of this study is the brand reputation management of the Natural Bengkulu logo as a visual identity that reflects the richness of local nature and culture. Data were collected through in-depth interviews with related parties, observations, and document reviews. The results of the study indicate that the Natural Bengkulu logo brand reputation management strategy implemented by the Bengkulu Provincial Tourism Office has succeeded in significantly increasing the visibility and attractiveness of regional tourism. By implementing seven components of reputation management including reputation template adjustment, reputation audit from internal and external perspectives, reputation capital goal setting, accountability formula, reputation management plan, annual audit and assessment, and stakeholder mapping, this strategy has created a positive and consistent image in the eyes of the public.